Effect of Vernonia amygdalina leaf meal on growth performance, intestinal mucosa activity, digestive enzymes, absorption capacity, and immunity in broiler chickens - B.M. Tokofai; B.M. Orounladji; K. Idoh; O.E. Oke; A. Agbonon (Journal of Applied Animal Nutrition)
Gut health is multifaceted and is largely influenced by the rearing environment and the diet. The use of phytochemicals rich in phenolics and flavonoids can improve the digestive health of chickens and lead to better growth performance. The aim of this study was to examine the effects of dietary Vernonia amygdalina leaf meal (VALM) on growth performance, digestive enzyme activities, absorption function, organ weights and immunity of broilers. Two hundred and forty, one-day-old male Cobb 500 broiler chicks were randomly divided into four groups: an unsupplemented control and VA-1, VA-3 and VA-5 receiving VALM incorporation at concentrations of 1, 3 and 5 g/kg, respectively. Each treatment had six replicates of 10 chickens. On d 42, six chickens per replicate were isolated and euthanised. Digesta from the jejunal segments (10 cm) was collected for analysis of the digestive enzymes. The remaining digesta was then washed out with ice-cold phosphate-buffered saline before the jejunal segments (10 cm) were opened longitudinally to collect the mucosa by scraping. For the preparation of the homogenate, intestinal mucosa samples were homogenised with 154 mmol/l of ice-cold sodium chloride solution and centrifuged at 4 °C for 900 s. To determine immunoglobulins, glutathione and D-xylose, the supernatant was extracted and stored at -20 °C. Supplementation with VALM did not significantly influence the relative weights of organs in the different treatments. However, VALM at 3 g/kg caused a significant increase in amylase and trypsin concentration (P<0.05). Immunoglobulin A and intestinal secretory immunoglobulin G concentrations were significantly improved (P<0.05) in the birds fed 3 g/kg VALM. This supported the premise that 3 g/kg VALM in feed can improve gastric immunity status and digestive enzyme secretion.